2018
DOI: 10.1007/s11738-018-2613-z
|View full text |Cite
|
Sign up to set email alerts
|

How the surface properties affect the nanocytotoxicity of silver? Study of the influence of three types of nanosilver on two wheat varieties

Abstract: The influence of silver nanoparticles on calli cells of stress tolerant-Parabola and stress sensitive-Raweta wheat genotypes (Triticum aestivum L.) was studied. Three types of silver nanoparticles (AgNPs) were tested: cystamine-stabilized (positively charged), unmodified, synthesized using sodium borohydride and citrate-stabilized AgNPs, both negatively charged. Physicochemical properties of silver nanoparticles were investigated by: UV-Vis spectroscopy, dynamic light scattering used for electrophoretic mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In a previous study, the authors indicated that the dispersion of zinc oxide nanoparticle in E3 medium was significantly reduced and formed aggregates, leading to a size of particles that exceeded the defined nanoscale range (1-100 nm), which may have affected the penetration through the chorion [61]. E3 medium, a multivalent inorganic salt solution, has been reported to trigger the instability of nanoparticles [62]; thus, the high ionic strength solution could contribute to the aggregation of AgNPs as demonstrated previously [63] and in our current study.…”
Section: Discussionmentioning
confidence: 66%
“…In a previous study, the authors indicated that the dispersion of zinc oxide nanoparticle in E3 medium was significantly reduced and formed aggregates, leading to a size of particles that exceeded the defined nanoscale range (1-100 nm), which may have affected the penetration through the chorion [61]. E3 medium, a multivalent inorganic salt solution, has been reported to trigger the instability of nanoparticles [62]; thus, the high ionic strength solution could contribute to the aggregation of AgNPs as demonstrated previously [63] and in our current study.…”
Section: Discussionmentioning
confidence: 66%
“…Compared to AgNP-citrate and -PVP, BPEI-coated AgNPs were found to be more biocidal for both Escherichia coli and Daphnia magna due to their smaller particle size and greater charge differences between the AgNP surface and the biologic surface, thus leading to higher attractive forces and potentially promoting the toxicity [52]. Significantly higher toxicity of positively charged AgNPs was also reported for tobacco plants exposed to AgNP-CTAB compared to AgNP-PVP and AgNP-citrate [17] and wheat calli treated with AgNP-cystamine (carrying a positive charge) compared to AgNP-citrate [53]. Furthermore, the significantly higher toxicity of positively charged AgNPs compared to the also positively charged Ag + ions from AgNO 3 found in the study of El Badawy et al [50] and in our study, supports the idea that physical interaction, which induces cellular membrane damage, could be the primary mechanism for AgNPs toxicity not just the chemical effect caused by Ag + ions alone.…”
Section: Discussionmentioning
confidence: 94%
“…Consequently, nanoparticles may affect the development, metabolism, and phenotype of plants. Interestingly, the impact of nanoparticles on plant growth and development strongly depends on the chemical composition of NPs, their size, shape, surface area, surface coatings, concentration, type of synthesis (chemical or biosynthesis), solvent applied, as well as the plant itself; its genotype, age, developmental stage, or chemical milieu of the cell (Barrena et al 2009;Dietz and Herth 2011;Syu et al 2014;Vannini et al 2014;Barbasz et al 2018). An increase in shoot and root length, leaf surface, and protein content in common bean (Phaseolus vulgaris L.) and corn (Zea mays L.) were reported after treating the in vivo-grown plants with low concentrations of AgNPs (20-60 ppm).…”
Section: Introductionmentioning
confidence: 99%